Stabilized hot melt pressure sensitive adhesive
By adding dialkyldithiocarbamate to the binder as a stabilizer for PPO, the problem of oxidation and degradation of PPO in the SIS block copolymer was solved, and the stability of the performance of the binder and the effect of high temperature resistance was achieved.
Patent Information
- Application Number
- CN202380057236.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-18
- Publication Date
- 2025-03-18
AI Technical Summary
Polyphenylene ether (PPO) in polystyrene-isoprene-styrene (SIS) block copolymer is prone to oxidation and degradation at high temperatures, resulting in loss of adhesive performance.
The addition of dialkyldithiocarbamate as a stabilizer for PPO in the binder significantly reduces the oxidative degradation of PPO in the SIS block copolymer.
Effectively stabilizes PPO, prevents the oxidative degradation of SIS block copolymers, and maintains the performance characteristics of the adhesive, especially under high temperature conditions.
Smart Images

Figure CN119654378A_ABST
Abstract
Description
Background Art
[0001] Adhesives are used in a variety of marking, fixing, protecting, sealing and masking applications. One type of adhesive, pressure-sensitive adhesives, is particularly preferred for many applications. Pressure-sensitive adhesives ("PSAs") are well known to those of ordinary skill in the art and have certain properties at room temperature (e.g., 23° C.), including: (1) strong and permanent tack, (2) adhesion without exceeding finger pressure, (3) the ability to remain on an adherend, and (4) sufficient cohesive strength. Materials that have been found to work well as pressure-sensitive adhesives are polymers that are designed and formulated to exhibit the desired viscoelastic properties, thereby achieving the desired balance of tack, peel adhesion, and shear strength. The characteristics of PSAs are described, for example, in Encyclopedia of Polymer Science and Engineering, Vol. 13, Wiley-Interscience Publishers (New York, 1988) and Encyclopedia of Polymer Science and Technology, Vol. 1, Interscience Publishers (New York, 1964).
[0002] Known pressure-sensitive adhesives can be prepared by mixing elastomers and suitable tackifiers. The elastomer that can be used to prepare PSA includes styrene block copolymers, which include polymerized glassy styrene blocks and polymerized rubbery blocks (e.g., polyisoprene). Radiated styrene block copolymers are a subset of styrene block copolymers, in which elastomers have multi-arm structures rather than linear structures. At ambient temperature, styrene blocks and rubbery blocks are microphase separated into discrete but connected domains to obtain a thermally reversible elastomeric structure. Tackifiers such as, for example, rosin esters can convert styrene block copolymers from elastomeric materials into viscoelastic materials. A given tackifier can be compatible (i.e., miscible) with glassy blocks, rubbery blocks, or at least partially compatible with these two types of blocks. Selective compatibility enables a given tackifier to change the characteristics of the rubbery or glassy domains of microphase separation structures when added to styrene block copolymers. Summary of the invention
[0003] Provided herein are adhesives comprising a SIS block copolymer, PPO, and a dialkyl dithiocarbamate, which are excellent PPO stabilizers and can significantly reduce oxidative degradation of PPO in SIS block copolymer adhesive formulations.
[0004] In one aspect, a high performance hot melt pressure sensitive adhesive ("hmPSA") is provided, the hmPSA comprising 40 weight percent ("wt. %) to 60 wt. % of a block copolymer comprising polystyrene and polyisoprene, 30 wt. % to 60 wt. % of a first tackifying resin, 1 wt. % to 15 wt. % of a polyphenylene ether tackifier, and 0.5 wt. % to 5 wt. % of a stabilizer represented by the following structure I:
[0005]
[0006] Where R 1 , R 2 , R 3 and R 4 Each of is independently selected from the group consisting of a C1 to C5 alkyl group, an unsubstituted phenyl group, a substituted phenyl group, an unsubstituted benzyl group, a substituted benzyl group, and combinations thereof.
[0007] In another aspect, a tape is provided, comprising: a backing; and a pressure-sensitive adhesive layer disposed on the backing and composed of the disclosed hmPSA composition.
[0008] In another aspect, a bonding assembly is provided, comprising: a low surface energy substrate; and a pressure sensitive adhesive layer disposed on the low surface energy substrate and composed of the disclosed hmPSA composition.
[0009] In another aspect, a method of making a stabilized hot melt pressure sensitive adhesive is provided.
[0010] As used in this article:
[0011] The term "ambient temperature" means at a temperature of 25°C;
[0012] The term "compatible with" means miscible with or soluble in;
[0013] The term "substituted" used in conjunction with a molecule or an organic group refers to a state in which one or more hydrogen atoms contained therein are replaced by one or more non-hydrogen atoms;
[0014] The term "tackifier" is used interchangeably herein with the term "tackifying resin" and refers to a high glass transition Tg resin used as an additive to increase the Tg of an adhesive while reducing the storage modulus; and
[0015] The term "unsubstituted" used in connection with a molecule or an organic group refers to a state in which none of the hydrogen atoms contained therein is substituted with one or more non-hydrogen atoms.
[0016]
[0026] A further understanding of the features and advantages of the present disclosure will be achieved upon consideration of the detailed description and the appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a perspective view of a ribbed plastic substrate for use with the disclosed adhesive composition.
[0018] Figure 2 and Figure 3 is a side elevation view of an adhesive-backed tape comprising the disclosed adhesive composition.
[0019] Figure 4 is a partial side view of a bonded assembly wherein the disclosed adhesive composition is used to bond Figure 1 of substrates to a different substrate.
[0020] Reference symbols used repeatedly in the specification and drawings are intended to represent the same or similar features or elements of the present disclosure. A large number of other modifications and embodiments may be designed by those skilled in the art, all of which are within the scope of the present invention and in accordance with the spirit of the principles of the present invention. The figures may not be drawn to scale. DETAILED DESCRIPTION
[0021] Reference will now be made to various embodiments of the presently disclosed subject matter.While the presently disclosed subject matter will be described in conjunction with the enumerated claims, it will be understood that the exemplary subject matter is not intended to limit the claims to the presently disclosed subject matter.
[0022] Unless the context clearly indicates otherwise, the terms "a", "an" or "the" are used to include one or more than one. Unless otherwise indicated, the term "or" is used to refer to a non-exclusive "or". The expression "at least one of A and B" has the same meaning as "A, B, or A and B". In addition, it should be understood that the words or terms used herein and not otherwise defined are used for descriptive purposes only and are not limiting. Any use of section headings is intended to facilitate understanding of the document and should not be construed as limiting; information related to a section heading may appear within or outside that section.
[0023] In order to meet the high temperature performance specifications of automotive and industrial manufacturers producing articles containing styrene-isoprene-styrene ("SIS") block copolymers, it may be advantageous to include polyphenylene oxide ("PPO") as a high Tg material to reinforce the styrene domains of these SIS block copolymers. However, PPO is particularly susceptible to oxidative degradation at high temperatures. The resulting oxidative degradation reactions of PPO may degrade or depolymerize the isoprene midblock of the SIS base resin, causing the adhesive containing the SIS base resin to lose some of its necessary performance characteristics, such as stretch release properties that may be sensitive to this type of aging.
[0024] It has been unexpectedly discovered that certain dialkyl dithiocarbamates, when added to adhesives containing SIS block copolymers and PPO, are excellent PPO stabilizers and can significantly reduce oxidative degradation of SIS block copolymers in PPO-containing adhesive formulations, i.e., degradation that results in a loss of performance characteristics when the adhesive is exposed to heat and oxygen.
[0025] The present disclosure provides a high performance hot melt pressure sensitive adhesive ("hmPSA") comprising 40 weight percent ("wt. %) to 60 wt. % of a block copolymer comprising polystyrene and polyisoprene, 30 wt. % to 60 wt. % of a first tackifying resin, 1 wt. % to 15 wt. % of a polyphenylene ether tackifier, and 0.5 wt. % to 5 wt. % of a stabilizer represented by the following structure I:
[0026]
[0027] Where R 1 , R 2 , R 3 and R 4 Each of is independently selected from the group consisting of a C1 to C5 alkyl group, an unsubstituted phenyl group, a substituted phenyl group, an unsubstituted benzyl group, a substituted benzyl group, and combinations thereof.
[0028] Block copolymers
[0029] The block copolymers that can be used in the embodiments of the present disclosure are known in the art. The block copolymer can be a single block copolymer or a mixture of two or more block copolymers. At least one block copolymer in the block copolymer component is a block copolymer containing isoprene rubber (or low T g block) and two or more styrene glassy blocks (or high T g In some embodiments, the block copolymer component may also include at least a second styrene block copolymer, the second styrene block copolymer comprising an isoprene rubber block (or a low Tg block) and two or more styrene glassy blocks (or high T g Block), wherein such additional styrene block copolymers can be linear block copolymers or radial block copolymers as described below.
[0030] At the working temperature of the adhesive, the block copolymer component is microphase separated into ordered nanoscale domains, which include rubbery block domains and glassy block domains. This ordered structure provides useful and unique physical properties for the block copolymer component. When microphase separated, these copolymers form elastic, dimensionally stable solids that show significant shear strength. Unlike chemically crosslinked rubbers, these materials (also referred to herein as "hot-melt processable" adhesives) can be reversibly melted and resolidified by heat because there is little or no covalent crosslinking during the entire life of the adhesive. In general, the upper service temperature limit of formulations without PPO is limited to 70°C or lower, and therefore covalent crosslinking is generally used to increase the service temperature. However, including PPO can increase the upper service temperature limit to 80°C or even higher, while maintaining thermoplastic properties, and allowing reprocessing at high temperatures generally above 150°C. The ability to reprocess allows automatic distribution at the final manufacturing endpoint (e.g., using core-skin filaments and dispensers), and also allows reuse or recycling of materials. In contrast, covalently crosslinked formulations are limited to strip forms with fixed / defined geometries.
[0031] The styrene block copolymer may be of the general formula (GR) m -G linear block copolymer, wherein G is a glassy block, R is a rubbery block, and m is an integer equal to or greater than 1. In some embodiments, the value of m can be in the range of 1 to 10, 1 to 5, 1 to 3, or in some embodiments, less than, equal to, or greater than 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. In a preferred embodiment, the linear block copolymer is a triblock copolymer of formula GRG, wherein in formula (GR) m -G, the variable m is equal to 1.
[0032] Alternatively, the styrene block copolymer may be of the general formula (GR) n -Y star-shaped (also known as radial or multi-arm) block copolymer, wherein each R and G are the same as defined above, n is an integer equal to at least 3, and Y is the residue of a multifunctional coupling agent used to form the star-shaped block copolymer. The variable n represents the number of arms in the star-shaped block copolymer, and can be in the range of 3 to 10, 3 to 8, 3 to 6, or in some embodiments, less than, equal to or greater than 3, 4, 5, 6, 7, 8, 9 or 10.
[0033] In both the linear block copolymer form and the radial block copolymer form of the styrenic block copolymer, the glassy blocks may have the same or different molecular weights. Similarly, if more than one rubbery block is present, the rubbery blocks may have the same or different molecular weights.
[0034] Generally, each rubbery block has a glass transition temperature (T g ). For example, the glass transition temperature can be less than 20°C, less than 0°C, less than -10°C, less than -20°C, less than -40°C, less than -60°C, or in some embodiments, less than, equal to or greater than -60°C, -55°C, -50°C, -45°C, -40°C, -35°C, -30°C, -25°C, -20°C, -15°C, -10°C, -5°C, 0°C, 5°C, 10°C, 15°C or 20°C. The glass transition temperature can be determined using conventional methods known in the art, including, for example, differential scanning calorimetry and / or dynamic mechanical analysis.
[0035] Each rubbery block in a linear or radial block copolymer is typically a polymerization product of a first polymerized conjugated diene, a hydrogenated derivative of a polymerized conjugated diene, or a combination thereof. Conjugated dienes often contain 4 to 12 carbon atoms. Conjugated dienes may include, but are not limited to, butadiene, isoprene, 2-ethylbutadiene, 1-phenylbutadiene, 1,3-pentadiene, 1,3-hexadiene, 2,3-dimethyl-1,3-butadiene, and 3-ethyl-1,3-hexadiene.
[0036] Each rubbery block can be a homopolymer or a copolymer. The rubbery block is typically, for example, poly(butadiene), poly(isoprene), poly(2-ethylbutadiene), poly(1-phenylbutadiene), poly(1,3-pentadiene), poly(1,3-hexadiene), poly(2,3-dimethyl-1,3-butadiene), poly(3-ethyl-1,3-hexadiene), poly(ethylene / propylene), poly(ethylene / butylene) or poly(isoprene / butadiene). In many embodiments, the R block is polybutadiene, polyisoprene, poly(isoprene / butadiene), poly(ethylene / butylene) or poly(ethylene / propylene).
[0037] The glass transition temperature of each glassy block is typically at least 50°C, at least 60°C, at least 70°C, at least 80°C, at least 90°C, at least 100°C, at least 105°C, at least 110°C, or in some embodiments, less than, equal to, or greater than 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, or 110°C.
[0038] Each glassy block in a linear or radial block copolymer is typically a polymerization product of a monovinyl aromatic monomer. The monovinyl aromatic monomer typically contains, for example, at least 8 carbon atoms, at least 10 carbon atoms, or at least 12 carbon atoms and up to 18 carbon atoms, up to 16 carbon atoms, or up to 14 carbon atoms. Exemplary monovinyl aromatic monomers include, but are not limited to, styrene, vinyl toluene, α-methylstyrene, 2,4-dimethylstyrene, ethylstyrene, 2,4-diethylstyrene, 3,5-diethylstyrene, α-2-methylstyrene, 4-tert-butylstyrene, and 4-isopropylstyrene.
[0039] Each glassy block may be a homopolymer or a copolymer. The glassy block may be poly(styrene), poly(vinyltoluene), poly(α-methylstyrene), poly(2,4-dimethylstyrene), poly(ethylstyrene), poly(2,4-diethylstyrene), poly(3,5-diethylstyrene), poly(α-2-methylstyrene), poly(4-tert-butylstyrene), poly(4-isopropylstyrene) and copolymers thereof.
[0040] In some embodiments, the glassy block is a polystyrene homopolymer or a copolymer derived from a mixture of styrene and a monomer that is compatible with styrene, i.e., a monomer that is miscible with styrene. In most cases where the glassy phase is a copolymer, at least 50 weight percent of the monomer units are derived from styrene. For example, at least 60 weight percent, at least 70 weight percent, at least 80 weight percent, at least 90 weight percent, at least 95 weight percent, at least 98 weight percent, at least 99 weight percent of the monomer units in the glassy block are derived from styrene.
[0041] Glassy blocks can account for 5 to 50 weight percent of the styrene block copolymer. If the fraction of glassy blocks is too low, the cohesive strength may be too low. On the other hand, if the fraction of glassy blocks is too high, the modulus may be too high (i.e., the composition may be too rigid and / or too elastic), and the resulting composition will not be effectively wetted on the substrate surface. Relative to the gross weight of the styrene block copolymer, the styrene copolymer may have 7% to 40%, 9% to 33%, 13% to 25%, or in some embodiments less than, equal to or greater than 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 27%, 30%, 32%, 35%, 37% or 40% styrene (or glassy blocks) content.
[0042] In addition to glassy blocks and rubbery blocks, styrene block copolymers as star block copolymers include multifunctional coupling agents. Coupling agents generally have multiple carbon-carbon double bonds, carbon-carbon triple bonds or other groups that can react with negative carbon ions of living polymers for forming star block copolymers. The multifunctional coupling agent can be aliphatic, aromatic, heterocyclic or a combination thereof. Examples include but are not limited to polyvinyl acetylene, diacetylene, di(methyl)acrylate (e.g., ethylene glycol dimethacrylate), divinylbenzene, divinylpyridine and divinylthiophene. Other examples include but are not limited to multifunctional silyl halides (e.g., tetrafunctional silyl halides), polyepoxides, polyisocyanates, polyketones, polyanhydrides, polyalkenyls and dicarboxylates.
[0043] The weight average molecular weight of styrene block copolymers is generally not greater than 1,200,000 g / mol. If the weight average molecular weight is too high, the copolymer will be difficult to use in the preparation of pressure-sensitive adhesive compositions because a high concentration of organic solvent will be required for solution coating. If melt processed, the copolymer will be difficult to extrude due to its high melt viscosity and will be difficult to blend with other materials. In contrast, too low molecular weight can result in a pressure-sensitive adhesive having an unacceptably low cohesive strength.
[0044] The weight average molecular weight of the styrene block copolymer may be no greater than 1,000,000 g / mol, no greater than 900,000 g / mol, no greater than 800,000 g / mol, no greater than 600,000 g / mol, or no greater than 500,000 g / mol. The weight average molecular weight of the styrene block copolymer is typically at least 75,000 g / mol, at least 100,000 g / mol, at least 200,000 g / mol, at least 300,000 g / mol, or at least 400,000 g / mol.
[0045] The weight average molecular weight of the styrene block copolymer may be 75,000 g / mol to 1,200,000 g / mol, 100,000 g / mol to 1,000,000 g / mol, 100,000 g / mol to 900,000 g / mol, 100,000 g / mol to 500,000 g / mol, or in some embodiments, less than, equal to, or greater than 75,000 g / mol; 80,000 g / mol; 85,000 g / mol; 90,000 g / mol; 95,000 g / mol; 100,000 g / mol; 110,000 g / mol; 120,000 g / mol; 130,000 g / mol; 140,000 g / mol; 150,000 g / mol; 160,000 g / mol 0g / mol; 170,000g / mol; 180,000g / mol; 190,000g / mol; 200,000g / mol; 220,000g / mol ;240,000g / mol; 250,000g / mol; 260,000g / mol; 280,000g / mol; 300,000g / mol; 350,0 00g / mol; 400,000g / mol; 450,000g / mol; 500,000g / mol; 600,000g / mol; 700,000g / mo l; 750,000g / mol; 800,000g / mol; 900,000g / mol; 1,000,000g / mol; or 1,200,000g / mol.
[0046] Some styrenic block copolymers have a glassy block that is a polystyrene and one or more rubbery blocks selected from the group consisting of polyisoprene, polybutadiene, poly(isoprene / butadiene), poly(ethylene / butylene), and poly(ethylene / propylene). Some even more specific styrenic block copolymers have a glassy block that is a polystyrene and one or more rubbery blocks selected from the group consisting of polyisoprene and polybutadiene. In some embodiments, the styrenic block copolymers have a glassy block that is a polystyrene and one or more rubbery blocks that are polyisoprene.
[0047] In some embodiments, the styrenic block copolymer is a first styrenic block copolymer, and the block copolymer component further comprises a second styrenic block copolymer that is a diblock copolymer. A diblock copolymer typically has a single glassy block and a single rubbery block, and can be represented herein by the chemical structure GR.
[0048] Including diblock copolymers can reduce the melt viscosity of pressure-sensitive adhesives and / or provide functionality similar to the functionality obtained when adding plasticizers. In some embodiments, diblock copolymers can increase the tackiness and low temperature performance of the resulting pressure-sensitive adhesive composition. Diblock copolymers can also be used to regulate the flow characteristics of pressure-sensitive adhesives. The amount of diblock can be selected to provide the flow characteristics of expectation, and the cohesive strength of the pressure-sensitive adhesive can not be significantly affected.
[0049] When describing the second styrenic block copolymer (ie, diblock copolymer), the same glassy blocks and rubbery blocks described with respect to the first styrenic block copolymer (eg, triblock and radial block copolymers) are applicable.
[0050] The styrene content of the diblock copolymer can be from 10 wt % to 50 wt %, from 10 wt % to 40 wt %, from 15 wt % to 50 wt %, from 15 wt % to 40 wt %, from 20 wt % to 50 wt %, from 20 wt % to 40 wt %, or in some embodiments, less than, equal to, or greater than 10 wt %, 12 wt %, 15 wt %, 17 wt %, 20 wt %, 22 wt %, 25 wt %, 27 wt %, 30 wt %, 32 wt %, 35 wt %, 37 wt %, or 40 wt %, relative to the total weight of the diblock copolymer.
[0051] The weight average molecular weight of the diblock copolymer may be 75,000 g / mol to 250,000 g / mol, 100,000 g / mol to 250,000 g / mol, 125,000 g / mol to 250,000 g / mol, 125,000 g / mol to 200,000 g / mol, or in some embodiments, less than, equal to, or greater than 75,000 g / mol; 80,000 g / mol; 85,000 g / mol; 90,000 g / mol; 95,000 g / mol; g / mol; 100,000g / mol; 110,000g / mol; 120,000g / mol; 130,000g / mol; 140,000g / mol; 150,000g / mol; 160,000g / m ol; 170,000g / mol; 180,000g / mol; 190,000g / mol; 200,000g / mol; 220,000g / mol; 240,000g / mol; or 250,000g / mol.
[0052] The styrene block copolymer component may comprise 1 to 30 weight percent of the diblock copolymer, based on the total weight of the diblock copolymer. In some embodiments, the diblock copolymer is present in an amount of 1 to 25 weight percent, 3 to 15 weight percent, 5 to 10 weight percent, or in some embodiments, less than, equal to, or greater than 1 weight percent, 2 weight percent, 3 weight percent, 4 weight percent, 5 weight percent, 7 weight percent, 10 weight percent, 12 weight percent, 15 weight percent, 17 weight percent, 20 weight percent, 22 weight percent, or 25 weight percent, relative to the total weight of the second styrene block copolymer.
[0053] In some embodiments, the styrene block copolymer component contains 70 wt % to 100 wt % of radial block copolymers and / or linear block copolymers (e.g., linear triblock copolymers) and 0 wt % to 30 wt % of diblock copolymers, 70 wt % to 99 wt % of radial block copolymers and / or linear block copolymers and 1 wt % to 30 wt % of diblock copolymers, 70 wt % to 90 wt % of radial block copolymers and / or linear block copolymers and 10 wt % to 30 wt % of diblock copolymers, 75 wt % to 100 wt % of radial block copolymers and / or linear block copolymers and 0 wt % to 25 wt % of diblock copolymers, 75 wt % to 99 wt % of radial block copolymers and / or linear block copolymers and 1 wt % to 30 wt % of diblock copolymers, 9 wt % of radial block copolymers and / or linear block copolymers and 1 wt % to 25 wt % of diblock copolymers, 75 wt % to 90 wt % of radial block copolymers and / or linear block copolymers and 10 wt % to 25 wt % of diblock copolymers, 80 wt % to 100 wt % of radial block copolymers and / or linear block copolymers and 0 wt % to 20 wt % of diblock copolymers, 80 wt % to 99 wt % of radial block copolymers and / or linear block copolymers and 1 wt % to 20 wt % of diblock copolymers, or 80 wt % to 90 wt % of radial block copolymers and / or linear block copolymers and 10 wt % to 20 wt % of diblock copolymers.
[0054] In many embodiments, the styrenic block copolymer component contains 70 wt % to 100 wt % linear triblock copolymer and 0 wt % to 30 wt % diblock copolymer, 70 wt % to 99 wt % linear triblock copolymer and 1 wt % to 30 wt % diblock copolymer, 70 wt % to 95 wt % linear triblock copolymer and 5 wt % to 30 wt % diblock copolymer, or 70 wt % to 90 wt % triblock copolymer and 10 wt % to 30 wt % diblock copolymer.
[0055] The block copolymer component can be present in the adhesive composition in any suitable amount. For example, relative to the gross weight of the composition, the block copolymer component can be present in an amount of 40 % by weight to 60 % by weight, 45 % by weight to 55 % by weight, or in some embodiments, less than, equal to or greater than 40 % by weight, 41 % by weight, 42 % by weight, 43 % by weight, 44 % by weight, 45 % by weight, 46 % by weight, 47 % by weight, 48 % by weight, 49 % by weight, 50 % by weight, 51 % by weight, 52 % by weight, 53 % by weight, 54 % by weight, 55 % by weight, 56 % by weight, 57 % by weight, 58 % by weight, 59 % by weight or 60 % by weight.
[0056] Suitable materials for use as the styrenic block copolymer component, alone or in combination, are commercially available from Kraton Performance Polymers (Houston, TX, USA) under the trade name KRATON (e.g., KRATON D1161P, D1118, D1119, A1535), commercially available from Dynasol (Houston, TX, USA) under the trade name SOLPRENE (e.g., SOLPRENE S-1205), commercially available from Zeon Chemicals (Louisville, KY, USA) under the trade name QUINTAC, commercially available from LCY Group (Taipei, Taiwan, China) under the trade name GLOBALPRENE, and commercially available from TSRC Corporation (TSRC) under the trade names VECTOR and TAIPOL. It was commercially available from Sigma-Aldrich Corporation (New Orleans, LA, USA).
[0057] The pressure-sensitive adhesive may contain 40 to 60 wt % of the styrene block copolymer component, based on the total weight of the pressure-sensitive adhesive. If the amount of the styrene block copolymer component is too low, the tackifier content may be too high and the resulting T g If the amount of the styrene block copolymer component is too high, the composition may have a modulus that is too high (e.g., the composition may not be a pressure sensitive adhesive), particularly in the absence of a plasticizer. If the amount of the styrene block copolymer component is too high, the composition may have a modulus that is too high (e.g., the composition may be too rigid and / or too elastic), and the composition may not wet properly when applied to a substrate.
[0058] %, 53 wt %, 54 wt %, 55 wt %, 56 wt %, 57 wt %, 58 wt %, 59 wt %, or 60 wt %, or in some embodiments, less than, equal to, or greater than 40, 41 wt %, 42 wt %, 43 wt %, 44 wt %, 45 wt %, 46 wt %, 47 wt %, 48 wt %, 49 wt %, 50 wt %, 51 wt %, 52 wt %, 53 wt %, 54 wt %, 55 wt %, 56 wt %, 57 wt %, 58 wt %, 59 wt %, or 60 wt %.
[0059] Tackifying resin
[0060] Tackifying resins useful in embodiments of the present disclosure are known in the art.The provided adhesive compositions contain a first tackifying resin that is compatible with the rubbery mid-block segments of the styrenic block copolymer and comprises a hydrocarbon.
[0061] The first tackifier is compatible with the rubbery block of the styrene block copolymer and can be an aliphatic hydrocarbon tackifier, a terpene tackifier, a terpene phenolic tackifier, or a mixture thereof. The hydrocarbon tackifier is preferably compatible with the rubbery block of the block copolymer component, but not compatible with the glassy block thereof. When incorporated into the adhesive composition in a suitable amount, the addition of the hydrocarbon tackifier can improve the adhesion of the adhesive composition to low surface energy substrates.
[0062] The compatibility of the tackifier with the rubbery block can be determined by measuring the effect of the tackifier on the glass transition temperature of the rubbery block. If the tackifier is compatible, it will generally increase the glass transition temperature of the rubbery block. Tackifiers such as hydrocarbon tackifiers, terpene tackifiers, and terpene phenolic tackifiers tend to be particularly compatible with rubbery blocks.
[0063] Useful hydrocarbon tackifiers include aliphatic hydrocarbon resins. In some embodiments, the aliphatic hydrocarbon is fully hydrogenated. Examples of hydrocarbon tackifiers include, but are not limited to, those commercially available under the tradename ARKON (e.g., ARKON P140 and ARKON P125) from Arakawa Europe GmbH, Eschborn, Germany, under the tradename REGALREZ (e.g., REGALREZ 1126) from Eastman Chemical Co., Kingsport, Tennessee, REGALITE (e.g., REGALITE 1125) from Eastman Chemical Co., Spring, Texas, under the tradename ESCOREZ (e.g., ESCOREZ 5615, 5320, 1315, 1304, 5637, and 5340) from ExxonMobil Chemical Company, Spring, Texas, under the tradename OPPERA (e.g., OPPERA PR 100A) from Exxon, NEVTAC (e.g., NEVTAC 115) from Neville Chemical Company, Pittsburgh, PA, H-REZ (e.g., H-REZC9 125H) from NUROZ LLC, Miami, FL, ALPHATAC (e.g., ALPHATACK 115) from RE Carroll, Inc., Ewing, NJ, RESINALL (e.g., RESINALL 1030 and 1030A) from Resinall Corporation, Severn, NC, and FUCLEAR (e.g., FUCLEAR FP-125 and FP-100) were those commercially available from United Performance Materials Corporation, Taipei, Taiwan, China.
[0064] Other suitable hydrocarbon tackifiers include terpenes. Terpenes include polyterpenes (e.g., α-pinene-based resins, β-pinene-based resins, and limonene-based resins). Examples of terpenes include those commercially available under the trade name CLEARON (e.g., CLEARON P150 and P135) from Yasuhara Chemical Company, Ltd., Hiroshima, Japan.
[0065] Other suitable first tackifiers include terpene phenolic resins, also known as terpene phenolic tackifiers or terpene phenolics. Example terpene phenolics include, but are not limited to, those commercially available from Yasuhara Chemical Co., Ltd. of Hiroshima, Japan under the trade name YS POLYSTER (e.g., POLYSTER T115, T160, T130, S145, and G150).
[0066] The hydrocarbon tackifier may have a softening point of 80° C. to 160° C., 100° C. to 150° C., 115° C. to 145° C., or in some embodiments, less than, equal to, or greater than 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C., 120° C., 125° C., 130° C., 135° C., 140° C., 145° C., 150° C., 155° C., or 160° C. In some embodiments, the hydrocarbon tackifier is an aliphatic polymer to provide the desired compatibility with the rubbery block and to provide minimal compatibility with the glassy block.
[0067] The amount of the first tackifier present in the adhesive composition can be 30% to 60%, 30% to 55%, 35% to 60%, or in some embodiments, less than, equal to, or greater than 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, relative to the total weight of the adhesive composition. If the amount of the first tackifier is too high, the glass transition temperature of the resulting composition may be too high so that it cannot be used as a pressure sensitive adhesive. However, if the amount of the first tackifier is too low, the modulus may be too high and the composition may not wet adequately on the substrate surface.
[0068] Polyphenylene Oxide ("PPO") Tackifier
[0069] The provided adhesive composition also includes at least a second tackifier that is compatible with the glassy endblock segments and includes a polyphenylene oxide (also referred to herein as "polyphenylene ether") tackifier. In some embodiments, the phenyl ether polymer contains repeating units shown in the following structure II:
[0070]
[0071] Wherein each X is independently a monovalent substituent selected from the group consisting of hydrogen, halogen, hydrocarbon, halohydrogen, hydrocarbonoxy, and halohydrocarbonoxy having at least two carbon atoms between the halogen atom and the phenyl core. In some embodiments, each X is a methyl group.
[0072] The inclusion of a polyphenylene ether tackifier can significantly increase the operating temperature of the adhesive by increasing the glass transition temperature of the glassy block of the block copolymer component. The polyphenylene ether resin has a Tg within a range that allows the resin to be compatible with the glassy block copolymer component. g Suitable polyphenylene ether resins are commercially available under the trade designation NORYL (eg, NORYL SA90 and SA120) from SABIC Americas, Houston, TX, United States.
[0073] The polyphenylene ether resin can provide the tackifier with a softening point of 100°C to 230°C, 120°C to 220°C, 135°C to 175°C, or in some embodiments, less than, equal to, or greater than 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, and 230°C.
[0074] The polyphenylene ether resin may have a weight average molecular weight (MW) of 1,000 g / mol to 50,000 g / mol, 1,000 g / mol to 45,000 g / mol, 1,000 g / mol to 40,000 g / mol, 1,000 g / mol to 35,000 g / mol, 1,000 g / mol to 30,000 g / mol, 1,000 g / mol to 25,000 g / mol, 2,000 g / mol to 10,000 g / mol, 4,000 g / mol to 8,000 g / mol. w ), or in some embodiments, less than, equal to, or greater than 1,000 g / mol; 1,200 g / mol; 1,500 g / mol; 1,700 g / mol; 2,000 g / mol; 2,500 g / mol; 3,000 g / mol; 3,500 g / mol; 4,000 g / mol; 4,500 g / mol; 5,000 g / mol; 5,500 g / mol; 6,000 g / mol; 6,500 g / mol; 7,000 g / mol; 7,500 g / mol; 8,000 g / mol; 8,500 g / mol; 9,000 g / mol; 9,500 g / mol; 10,000 g / mol g / mol; 11,000 g / mol; 12,000 g / mol; 13,000 g / mol; 14,000 g / mol; 15,000 g / mol; 16,000 g / mol; 17,000 g / mol; 18,000 g / mol; 19,000 g / mol; 20,000 g / mol; 21,000 g / mol; 22,000 g / mol; 23,000 g / mol; 24,000 g / mol; 25,000 g / mol; 30,000 g / mol; 35,000 g / mol; 40,000 g / mol; 45,000 g / mol; or 50,000 g / mol. If the molecular weight of the polyphenylene ether resin is too low, the Tg will not be high enough and it may become soluble in the midblock domain. If the molecular weight of the polyphenylene ether resin is too high, this may cause processing challenges in melting the PPO and making the PPO miscible with the styrene component.
[0075] The second tackifier may be partially or completely composed of one or more polyphenylene ether resins. The amount of the second tackifier present in the adhesive composition is usually less than the amount of the first tackifier, and relative to the gross weight of the adhesive composition, can be 1 wt % to 15 wt %, 2 wt % to 12 wt %, 4 wt % to 8 wt %, or in some embodiments, less than, equal to or greater than 1 wt %, 1.5 wt %, 2 wt %, 2.5 wt %, 3 wt %, 3.5 wt %, 4 wt %, 4.5 wt %, 5 wt %, 5.5 wt %, 6 wt %, 6.5 wt %, 7 wt %, 7.5 wt %, 8 wt %, 9 wt %, 10 wt %, 11 wt %, 12 wt %, 13 wt %, 14 wt % or 15 wt %.
[0076] Polyphenylene ether resins can be made by known methods. Suitable preparation methods are described in U.S. Patents 3,306,874 (Hay); 3,306,875 (Hay); 3,257,357 (Stamatoff); and 3,257,358 (Stamatoff).
[0077] Stabilizer
[0078] Stabilizers useful in embodiments of the present disclosure are known in the art and can be represented by the following structure III:
[0079]
[0080] Where R 1 , R 2 , R 3 and R 4 Each of R is independently selected from the group consisting of a C1 to C5 alkyl group, an unsubstituted phenyl group, a substituted phenyl group, an unsubstituted benzyl group, a substituted benzyl group, and combinations thereof. 1 , R 2 , R 3 and R 4 Each of is an n-butyl group. Such stabilizers are commercially available, for example, under the trade name VANLUBE EZ from RT Vanderbilt Holding Company, Norwalk, CT, United States.
[0081] The amount of stabilizer present in the adhesive composition can be 0.5 wt % to 5 wt %, or in some embodiments, less than, equal to, or greater than 0.5 wt %, 1 wt %, 1.5 wt %, 2 wt %, 2.5 wt %, 3 wt %, 3.5 wt %, 4 wt %, 4.5 wt %, or 5 wt %, relative to the total weight of the adhesive composition.
[0082] Optional additives
[0083] The adhesive composition of the present disclosure may optionally include one or more additives, such as, for example, tackifiers, plasticizers (e.g., polymers that are liquid at 25° C., mineral oils, polybutadiene homopolymers), antioxidants (e.g., hindered phenol compounds, phosphates, or derivatives thereof), UV absorbers (e.g., benzotriazole, oxazolic acid amides, benzophenones, or derivatives thereof), in-process stabilizers, anticorrosives, passivators, light stabilizers, processing aids, elastomeric polymers (e.g., other block copolymers), fillers (e.g., scavenger fillers, nanoscale fillers, transparent fillers), desiccants, crosslinking agents, pigments, organic solvents, and combinations thereof. In some preferred embodiments, the adhesive composition may include additives selected from the group consisting of fillers, polyolefin film-forming resins, pigments, second tackifying resins, UV stabilizers, foaming agents, toughening agents, heat stabilizers, secondary antioxidants, and combinations thereof. The total concentration of such additives is in the range of 0% to 60% by weight of the total adhesive composition.
[0084] In some embodiments, the adhesive composition can be a foaming composition. Foaming adhesive can be prepared by mixing physical foaming agent, chemical foaming agent, low-density filler or their combination into the adhesive composition. Available low-density filler includes, for example, hollow glass microspheres. Foaming adhesive composition not only reduces weight, but also may be advantageous in applications where the adhesive must conform to rough or irregularly shaped surfaces.
[0085] Adhesive components
[0086] The adhesives of the present disclosure can be prepared by methods known to those of ordinary skill in the relevant art. The ability to process these pressure sensitive adhesives from the melt makes them highly useful for bonding to molded articles made from polyolefins, and especially those with extreme surface features, such as Figure 1The ribbed molded part shown. A melt-processable adhesive can be heated to flow into the gaps within such a ribbed structure and then cooled to achieve high bond strengths that would not otherwise be achievable using conventional adhesive flat sheets, such as in systems including core-sheath filaments and core-sheath filament dispensers, such as those described, for example, in WO 2019 / 164678 (Nyaribo et al.) and WO 2021 / 12481 (Napierala et al.).
[0087] In one exemplary embodiment, adhesive backed tape 100 is shown in Figure 2 The adhesive-backed tape 100 includes a backing 102 and a pressure-sensitive adhesive 104 made from a provided adhesive composition. As shown, the pressure-sensitive adhesive 104 is present as a layer extending across and directly contacting the backing 102. Advantageously, no primer layer is required or present between the backing 102 and the pressure-sensitive adhesive 104.
[0088] The backing 102 can be made of any known material suitable for use as a tape backing. Suitable materials for the backing 102 include polymer foams and solid films made of polyolefins, such as polyethylene (including high-density polyethylene, low-density polyethylene, linear low-density polyethylene, and linear ultra-low-density polyethylene), polypropylene, and polybutylene; ethylene copolymers such as polyvinyl chloride (both plasticized and unplasticized) and polyvinyl acetate; olefin copolymers such as ethylene / methacrylate copolymers, ethylene / vinyl acetate copolymers, acrylonitrile-butadiene-styrene copolymers, and ethylene / propylene copolymers; acrylic polymers and copolymers; polyurethanes; and combinations thereof. If the backing 102 is a foam, it can be an open-cell foam or a closed-cell foam. In addition, the backing 102 can be made of a sticky or non-sticky material.
[0089] Figure 3 A double-sided tape 200 is shown that includes a first pressure-sensitive adhesive 204a disposed on a side of a backing 202 opposite to a side of a second pressure-sensitive adhesive 204b. This double-sided construction may be appropriately used, for example, when bonding two different substrates to each other. The second pressure-sensitive adhesive 204b may be made of the same adhesive as the first pressure-sensitive adhesive 204a or a different adhesive.
[0090] The provided adhesive compositions are melt processable, enabling them to be used to bond to substrates having uneven surfaces. Such applications are Figure 4 The bonding assembly 300 shown in FIG. The bonding assembly 300 shows a pressure sensitive adhesive 304 interposed between a first substrate 306 and a second substrate 308, wherein the second substrate 308 is a molded component having a plurality of raised ribs, such as Figure 1 shown.
[0091] As shown, the pressure sensitive adhesive 304 partially fills the cavities between the ribs of the second substrate 308, thereby allowing a larger bonding surface area and improved overall bond strength. This can be achieved by placing the adhesive composition in a molten form onto the second substrate 308, allowing the melt to penetrate into the ribbed structure, and then cooling the adhesive composition to cause microphase separation of the adhesive composition and obtain the pressure sensitive adhesive 304. The pressure sensitive adhesive 304 can then be adhered to the first substrate 306. Optionally, the cavities of the second substrate 308 can be completely filled with the pressure sensitive adhesive 304.
[0092] The order of the above steps may be different from that described above. For example, the adhesive composition can be arranged between the first substrate 306 and the second substrate 308 in a molten form, the first substrate 306 and the second substrate 308 are pressed together, and the adhesive composition is cooled to directly form the bonding assembly 300. Alternatively, the adhesive composition can be arranged between the second substrate 308 and a disposable release liner (not shown), the second substrate 308 and the release liner are pressed together, and then the adhesive composition is cooled to form the pressure-sensitive adhesive 304. Later, the pressure-sensitive adhesive 304 can be peeled off from the release liner and adhered to the first substrate 306, to form the bonding assembly 300.
[0093] In some embodiments, adhesive composition has a topological structured surface. The topological structured surface can be used to provide, for example, an adhesive composition layer, and the thickness of the adhesive composition layer varies according to its position on substrate. The topological structured surface can include an array of projections or depressions that are arranged on the surface of a plane. The projections or depressions can be continuous or discrete in nature. Projections or depressions can be randomized on the entire topological structured surface, or can be arranged according to a predetermined replica pattern with features that are regularly spaced apart from each other. This type of pattern includes a linear pattern and a hexagonal pattern.
[0094] By adhesive composition being arranged on the topologically structured stripping surface from polymer melt, and cooling said composition then so that adhesive is pressed into the topologically structured surface, thereby make adhesive composition have the surface of topologically structured.Advantageously, this type of adhesive can be the pressure-sensitive adhesive that can transport and / or store in this configuration.Pressure-sensitive adhesive can be peeled off from the stripping surface before use subsequently.
[0095] The above method is only exemplary, and by placing the adhesive composition into contact with a tool of suitable shaping, other methods of smoothing or shaping the adhesive composition can be used. If necessary, the adhesive composition can be smoothed, embossed or otherwise shaped after it is arranged on a peeling surface or substrate, after its microphase separation or both.
[0096] In the above embodiments, the adhesive composition is applied to the substrate as a hot melt PSA using an automated process. Automated methods include, for example, using a robotic arm to melt coat the PSA onto the substrate in a continuous or discontinuous manner.
[0097] Applications for the coated adhesive compositions are varied and may include, for example, bonding solutions for corrugated materials, flooring, laminates, foams, porous fabrics, packaging materials, bookbinding, disposable products such as diapers and hygiene products, appliances, box and carton sealing, shoe manufacturing, wire, wire bundles, and wire harnesses.
[0098] Either or both of the first substrate 206 and the second substrate 208 can be made of a low surface energy material such as a thermoplastic polyolefin. Suitable substrates can be provided in any suitable size or shape. In a useful application, the substrate is a varnish coating, such as a low surface energy varnish coating, such as can be provided on an aerospace or automotive exterior surface.
[0099] Objects and advantages of this disclosure are further illustrated by the following non-limiting examples, but the particular materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed to unduly limit this disclosure.
[0100] Example
[0101] Unless otherwise indicated, all parts, percentages, ratios, etc. in the examples and the remainder of this specification are by weight. Unless otherwise indicated, the materials used in the examples were obtained from commercial suppliers (e.g., Aldrich Chemical Co., Milwaukee, Wisconsin.) and / or prepared by known methods. The materials prepared in the examples were analyzed by NMR spectroscopy and were consistent with the given structures. As used below, "hr" = hour.
[0102] Materials used in the examples
[0103]
[0104]
[0105] Test Method
[0106] Rheological storage modulus test method :
[0107] The samples were analyzed using a DHR-3 parallel plate rheometer equipped with a Peltier plate attachment (TA Instruments, New Castle, DE, USA) to characterize the frequency dependent rheological properties of each sample. The rheological samples were formed into adhesive films approximately 1 mm thick between two LOPAREX 7350 / 7300 liners and subjected to different aging conditions, i.e., closed faced between the two liners or open faced on a single release liner. After aging, the samples were punched out with an 8 mm round die, removed from the release liner, centered on the 8 mm diameter parallel plate upper fixture of the rheometer, and compressed down onto the Peltier plate until the edge of the sample was aligned with the edge of the top plate.
[0108] The sample was conditioned at a test start temperature of 100°C under an axial force control of 150g with a sensitivity of + / -20g for 180 seconds. Then, a fixed strain of 5% was applied and the sample was tested from 10Hz to 0.1Hz at five points per decade. Although many physical parameters of the material are recorded during frequency testing, the storage modulus ("G'") at 1Hz is primary in the characterization of the polymer blends of the present disclosure. Rheological storage modulus values of 30kPa or higher are preferred.
[0109] Accelerated aging test method :
[0110] The samples were formed into adhesive films approximately 1 mm thick on LOPAREX 7350 / 7300 liners and subjected to different aging conditions (e.g., time, temperature, closed side or open side) in a forced air oven (Blue M, New Columbia, Pennsylvania). A particularly preferred aging condition was 105°C for 72 hours because it provided clear performance differences between the different antioxidant packages.
[0111] Lap Shear Test Method :
[0112] Cut and measure the PSA test sample of 2.54cm × 1.27cm sheet, and remove the first LOPAREX 7350 / 7300 liner. Then, use 2 times 6.8kg steel rollers to laminate the aluminum coupons onto the exposed adhesive surface in each direction. Then, remove the second LOPAREX 7350 / 7300 liner on the adhesive. The exposed PSA surface is laminated to the TPO test plate (named LYONDELL BASELL HIFAX TRC 779X), and use 2 times 6.8kg steel rollers to roll in each direction. Make the bonded sample stand the aging condition at 105 ℃, as specified in Table 3. Use a tensile tester equipped with 50 kilonewton load cells to implement lap shear test at room temperature, wherein the separation rate is 50 mm / min. Record the average maximum breaking force and use it to calculate the average lap shear strength in megapascals (MPa). 0.6MPa or greater lap shear strength values are desired.
[0113] Tensile peel test method :
[0114] PSA test samples (new or aged) were cut to 12.5 mm wide and a minimum of 6 cm long. The first LOPAREX 7350 / 7300 liner was removed, and the exposed surface of the PSA test sample was laminated to a 15.2 cm x 10.2 cm, 1.3 mm thick anodized aluminum test panel (Hiawatha Metalcraft, Inc., Minneapolis, MN, USA) so that at least 5 cm of adhesive was bonded to the panel 4 times with a 2.2 kg rubber roller. The long axis sample was oriented along the short axis of the aluminum panel, and the PSA test sample was oriented to protrude 1 cm from the edge of the aluminum panel, thereby creating a tab. The second LOPAREX 7350 / 7300 liner was removed, and a 2.5 cm piece of anodized aluminum foil was attached to the tab and folded to cover both sides of the PSA test specimen.
[0115] The test specimen was mounted into the lower chuck of a 5900 Series Instron (Instron, Norwood, MA, USA) load frame equipped with a 1 kg load cell. The specimen was oriented so that the longitudinal sample axis was vertical and the sample tab was centered and tightened in the top chuck. The induced tensile peel test was performed along an approximately 0 degree angle between the specimen and the tab. The upper chuck was moved at 100 cm per minute until the sample was completely debonded or cohesive failure occurred. Achieving a tensile peel of at least 5 cm from the aluminum specimen before failure was considered a pass value. Due to the high sample elongation and the maximum travel distance of the Instron load frame, a tensile peel of a maximum distance of 7.5 cm was tested.
[0116] Gel Permeation Chromatography ("GPC") Test Methods :
[0117] The molecular weight of the polymer mentioned in the present disclosure can be measured with gel permeation chromatography ("GPC") using polystyrene calibration standards. GPC is an established method in which polymers are separated according to molecular size, with the largest molecule eluting first. The elution graph (elugraph) is calibrated using commercially available polystyrene molecular weight standards (EASICAL, Agilent Technologies, Santa Clara, CA, California). The molecular weight of the polymer measured using the GPC so calibrated is the styrene equivalent molecular weight. The molecular weight reported here will be the polystyrene equivalent molecular weight from a GPC system utilizing tetrahydrofuran as a mobile phase and an Agilent 1260HPLC system (Agilent Technologies, Santa Clara, California, California) comprising two columns PLgel MIXED-B and MIXED-C in series and a refractive index detector.
[0118] When a polymer has a molecular weight distribution curve showing a single peak, it is often referred to as a unimodal polymer. A polymer having a curve showing two distinct peaks is often referred to as a bimodal polymer. A polymer having a curve showing three distinct peaks is often referred to as a trimodal polymer. Polymers having molecular weight distribution curves showing more than one peak may also be collectively referred to as multimodal polymers. For block copolymers, different GPC patterns are often attributed to specific polymer morphologies consisting of the primary block copolymer and specific fragments of the primary copolymer, which are different fragments of the copolymer that are the result of chain termination at different steps in the resin manufacturing process.
[0119] The term "peak molecular weight" ("Mp") is used herein. Mp refers to the styrene equivalent molecular weight of the highest peak as measured by GPC, and is defined as the peak of a GPC diagram of a defined region, which may be a total elution diagram before aging (i.e., 0 hr) or a specified mode of a multi-peak elution diagram. "dw / dlogMW" is the weight fraction of a sample with a corresponding styrene equivalent molecular weight (logM). For a given sample preparation, the dw / dlogMW value at Mp can be tracked to serve as a quantitative but indirect method for the relative amount of remaining material at that molecular weight. The dw / dlogMW value at Mp in Table 3 is reported as "GPC SIS Peak Height".
[0120] Preparation of adhesive samples :
[0121] Pressure sensitive adhesive (" PSA ") samples were prepared using the compositions in Table 2. All amounts shown are given in parts by weight (" pbw "). The materials were compounded using a co-rotating 30 mm twin screw mixer (Krauss-Maffei Berstorff, Munich, Germany) and subjected to 200 rpm (" rpm ") mixing for three minutes. The mixer and die temperature were set at 170 ° C. After mixing, PSA was melt-pumped through a slit die having a thickness of about 1 mm via a gear pump and a hose. PSA was cast onto 7350, i.e., the tight side (i.e., the high peel force side) of a LOPAREX 7350 / 7300 liner. Then, the 7300, i.e., the loose side (i.e., the low peel force side) of a second LOPAREX 7350 / 7300 liner was laminated to the exposed adhesive surface of the transfer tape. Then, the collected PSA was evaluated according to the above test method. The results are summarized in Table 3 below.
[0122]
[0123]
[0124] All references, patents and patent applications cited in the above patent applications are incorporated herein by reference in their entirety in a consistent manner. In the event of inconsistency or conflict between the incorporated references and the present application, the information in the foregoing description shall prevail. The foregoing description, which is given to enable a person of ordinary skill in the art to practice the present disclosure protected by the claims, should not be construed as limiting the scope of the present disclosure, which is defined by the claims and all equivalents thereof.
Claims
1. A composition comprising: 40 wt.% to 60 wt.% of a block copolymer comprising polystyrene and polyisoprene; 30 wt.% to 60 wt.% of a first tackifying resin; 1 wt.% to 15 wt.% of a polyphenylene ether tackifier; and 0.5 wt.% to 5 wt.% of a stabilizer represented by the following structure Where R 1 , R 2 , R 3 and R 4 Each of is independently selected from the group consisting of a C1 to C5 alkyl group, an unsubstituted phenyl group, a substituted phenyl group, an unsubstituted benzyl group, a substituted benzyl group, and combinations thereof.
2. The composition of claim 1, wherein the block copolymer comprises a polystyrene-polyisoprene-polystyrene copolymer selected from the group consisting of a polystyrene-polyisoprene-polystyrene triblock copolymer, a polystyrene-polyisoprene-polystyrene radial star block copolymer, and combinations thereof.
3. The composition of claim 1 or 2, wherein the first tackifying resin is selected from the group consisting of aliphatic hydrocarbon tackifiers, terpene tackifiers, terpene phenolic tackifiers, and combinations thereof.
4. The composition according to any one of claims 1 to 3, comprising 2 to 12 wt.%, optionally 4 to 8 wt.% of the polyphenylene ether tackifier.
5. The composition according to any one of claims 1 to 4, wherein R 1 , R 2 , R 3 and R 4 Each of is an n-butyl group.
6. The composition according to any one of claims 1 to 5, further comprising a plasticizer.
7. The composition of claim 6, wherein the plasticizer is selected from the group consisting of mineral oil, polybutadiene homopolymer, and combinations thereof.
8. The composition according to any one of claims 1 to 7, further comprising an additive selected from the group consisting of fillers, polyolefin film-forming resins, pigments, second tackifying resins, UV stabilizers, foaming agents, toughening agents, thermal stabilizers, secondary antioxidants, and combinations thereof.
9. An adhesive comprising the composition according to any one of claims 1 to 8.
10. The adhesive composition of claim 9, wherein the adhesive comprises a pressure sensitive adhesive.
11. The adhesive composition according to claim 9 or 10, wherein the adhesive composition is hot melt processable.
12. The adhesive composition of claim 11, wherein G' at 1 Hz at 100°C is greater than 25 kPa as measured by the Rheological Storage Modulus Test.
13. The adhesive composition of any one of claims 10 to 12, wherein the tensile peel at 23°C, 65% humidity is greater than 50 mm as measured by the tensile peel test.
14. The adhesive composition of any one of claims 10 to 13, wherein the SIS triblock peak height after aging at 105°C for 72 hours according to the accelerated aging test is at least 40% of the SIS triblock peak height of the unaged sample as measured by gel permeation chromatography test.
15. An article comprising the adhesive according to any one of claims 9 to 14.
16. The article of claim 15, wherein the article is a tape.
17. The article of claim 15, wherein the article is a core-sheath filament.
18. A bonded assembly comprising the adhesive according to any one of claims 9 to 14.
19. A method for preparing a stabilized hot melt pressure sensitive adhesive, the method comprising: 40 wt.% to 60 wt.% of a block copolymer comprising polystyrene and polyisoprene, 30 wt.% to 60 wt.% of a first tackifying resin, 1 wt.% to 15 wt.% of a polyphenylene ether tackifier, and 0.5 wt.% to 5 wt.% of a stabilizer represented by the following structure are combined Where R 1 , R 2 , R 3 and R 4 Each of is independently selected from the group consisting of a C1 to C5 alkyl group, an unsubstituted phenyl group, a substituted phenyl group, an unsubstituted benzyl group, a substituted benzyl group, and combinations thereof.
20. The process of claim 19, wherein the combining occurs in a twin screw extruder at a temperature greater than 160°C.
Citation Information
Patent Citations
Copolymers of polyphenylene ethers
US3257357A
Oxidation of phenols
US3306874A
Oxidation of phenols and resulting products
US3306875A
Core-sheath filaments and methods of printing an adhesive
WO2019164678A1
System performance monitoring method and apparatus, device, and storage medium
WO2021012481A1